Market share e rentabilidade: uma análise das estratégias dos bancos públicos e privados no período pós crise 2008 - Figueirêdo, Bruna Freire da Rocha (2018)
Brazilian private institutions continued to perform higher profit margins than state- owned banks even when they had withdrawn credit and lost their leadership in the domestic market, between the years of 2012 and 2013. This market changes occurred because, in the post-crisis period in 2008, private banks contracted credit supply and the state financial institutions acted to fill this gap with countercyclical measures. This high net income should not have been maintained because they slowed lending, the activity that leads more revenue. At that moment, the private banks opted for more liquid assets such as government bonds; which is liquid and less profitable. This assertion is based on the Keynes, where liquidity-premium matters in the assets choice. This paper analyzes the balance sheets and income statement, provided by the Central Bank of public and private banks between 2000 and 2016, considering the main aspects of the banking system's post-keynesian theory: liquid and liquid assets, liabilities, service revenues and administrative costs, additionally it presents the issue of taxes. In each of these general aspects, analysis’s variables were created, and profitability behavior were explored. The research always compares the behavior of private and public banks. The result indicates that the interest of financial assets of the public banks are consistent with the theory, however the result of the public banks was surpassed by the private ones by a set of strategies, notably: the administration of the liabilities, reflecting in the interest expense; the growth of service revenues and decrease in intermediation expenses. In the years of 2008 and 2015, was noticed a large influence in the deferred tax expense with a large credit in reversal of temporary difference